A Novel Printed Monopole Antenna With a Tapered-Line Resonator Loading - Dong Chen; Chen Zhang; Honglin Zhang; Chunlan Zhao (IEEE Access)
In this paper, a novel compact printed monopole antenna is presented. The antenna consists of a planar monopole antenna and a tapered-line resonator with inner coupled section, which works as a near-field resonant parasitic (NFRP) element. The resonant frequency can be decreased dramatically by the strong coupling between the resonator and the monopole antenna. Thus, the miniaturization of the antenna is realized. The simulated results show that the resonant frequency decreases from 2.98 GHz to 2.4 GHz and the electric length of the antenna is reduced from $0.32~λ $ to $0.25~λ $ by loading a tapered-line resonator as NFRP element. After theoretical analysis is presented, sample antenna is manufactured and measured to verify the predictive performance of the proposed antenna. The overall size of the antenna is only $44.6× 31.8× 0.5$ mm3, and the operation frequency of the antenna ranges from 2.59 GHz to 2.85 GHz (9.5%) based on $\vert $ S $11\vert \le -10$ dB, the gain is about 1.98dBi, which are in well agreement with the simulated results.